N-acetyl-cysteine in the therapy of HIV-positive patients - Dröge, Wulf; Breitkreutz, Raoul (Current opinion in clinical nutrition & metabolic care, 1999)
Randomly selected asymptomatic HIV-positive persons reveal, on average, a massive daily loss of sulphur, which appears to represent in first approximation the mean loss throughout the asymptomatic stage, and may explain the widely observed decrease in cyst(e)ine and glutathione levels. This sulphur loss is reasonably expected to lead, within a few years, to a life-threatening condition and may, therefore, contribute decisively to disease progression. Importantly, the rate of sulphur loss is not ameliorated by highly active antiretroviral therapy and may contribute to antiretroviral treatment failure. Several clinical trials on N-acetyl-cysteine treatment of HIV-positive patients have revealed various therapeutic effects, but did not meet the rigorous standards for approval by the health authorities.
Gesehen am 09.02.2021